SOLUBLE ADHESION MOLECULES IN CHILDREN WITH HEMOLYTIC UREMIC SYNDROME - T. E. Pankratenko; O. V. Moskalets; T. Yu. Abaseeva (Медицинская иммунология)
Atypical hemolytic uremic syndrom (aHUS) is a rare severe life-threatening form of thrombotic microangiopathy. aHUS is thought to be primarily mediated by dysfunctional complement regulation, due to mutations or genetic rearrangement of the complement components, or regulatory factors, as well as autoantibody production to the complement factors. These alterations promote uncontrolled complement activation by the alternative pathway on the surface of endothelial cells, followed by endothelial dysfunction, microthrombosis and organ damage, especially, renal pathology. Many studies showed that the biomarkers of endothelial activation/dysfunction including intercellular adhesion molecule type 1 (ICAM-1) and vascular cell adhesion molecule type 1 (VCAM-1) were associated with severe disease and could predict complications and clinical outcomes in different disorders. Increase of these biomarkers was observed in aHUS as well. Until recently, aHUS resulted in unfavorable outcomes, with high death rates in acute phase, and up to 2/3 patients progressed to the end-stage renal failure. Understanding the role of complement dysregulation in aHUS pathogenesis has led to major changes in therapeutic approaches. Eculizumab (a humanized anti-C5 monoclonal antibody) inhibits the terminal complement pathway. This drug has revolutionized treatment and improved prognosis in aHUS. Those patients who received eculizumab have shown sharp decreae in the C3 levels. However, the questions concerning duration of targeted therapy inremission still remains unclear.The aim of the present study was to evaluate serum С3, sICAM-1, sVCAM-1 levels in the children with aHUS remission supported by eculizumab maintenance treatment, or without it. Serum C3, sICAM-1 and sVCAM-1 levels were determined in 25 children with aHUS (14 treated with eculizumab and 15, without eculizumab). A control group included 17 children with a history of typical HUS. Serum levels of C3, sICAM-1 and sVCAM-1 were within normal age ranges in all the groups. The children treated with eculizumab showed decreased C3 levels (99±20 mg/l vs 112±15 mg/l, and 123±40 mg/l, respectively), and increased sICAM-1 levels (483±103 ng/ ml vs 343±50 ng/ml and 401±91 ng/ml, respectively) compared to other groups (p < 0.05). No differences in sVCAM-1 levels were revealed in the groups. Hence, no signs of subclinical complement activation or endothelial disfunction were revealed in the group free of eculizumab therapy. Normal C3, sICAM-1 and sVCAM-1 levels in blood indicate that normal endothelial state could be restored in aHUS, and this condition is maintained after discontinuation of the targeted therapy. Our results suggest that C3, sICAM-1 and sVCAM-1 monitoring may be useful for further management of these patients and for prediction of relapses.